La retòrica contrastiva. Una panoràmica de l’àrea - Fernández Polo, Francisco J. (Caplletra. Revista Internacional de Filologia, 2001)
The paper offers a comprehensive view of the field of Contrastive Rhetoric, its origins, its main hypotheses, its methodology as well as the application of its findings, principally, in the two areas of foreign language teaching and the resolution of problems in various contexts of «professional» communication. In the paper, a special effort is made to summarise and explain the results of those studies which specifically focus on the Spanish language. Finally, we will point at the existence of a series of methodological and even ideological problems which have haunted the discipline from the very beginning, and which have lately generated some concern among specialists both in and outside the field.